Marginal ulceration after Roux-en-Y gastric bypass surgery: characteristics, risk factors, treatment, and outcomes - Azagury, D. E.; Abu Dayyeh, B. K.; Greenwalt, I. T.; Thompson, C. C. (Endoscopy, 2011)
Background and study aims: Marginal ulcers are one of the most common complications after gastric bypass. Reported incidence varies widely (0.6–16 %) and pathogenesis is unclear. The aim of the present study was to describe characteristics, risk factors, management, and outcomes of endoscopically documented ulcers. Patients and methods: Data from all patients diagnosed with marginal ulcers at endoscopy between 2003 and 2010 were retrospectively reviewed. Results: A total of 103 patients with marginal ulcers presented with pain (63 %) and/or bleeding (24 %), a median of 22 months after surgery. Ulcers were located on the anastomosis (50 %) or the jejunum (40 %); sutures were visible in 35 %, and gastrogastric fistulae in 8 %. The mean pouch length was 5.6 cm. Diabetes (odds ratio [OR] 2.5; P = 0.03), smoking (OR 2.5; P = 0.02), and gastric pouch length (OR 1.2; P = 0.02) were significantly associated with marginal ulcer formation on univariate analysis; diabetes was significantly associated on multivariate analysis (OR 5.6; P = 0.003). The risk of developing a marginal ulcer decreased with time (OR 0.8; P < 0.01) and was not associated with the use of nonsteroidal anti-inflammatory drugs. At first endoscopic follow-up, 67 % of ulcers had healed. Recurrence occurred in four patients and nine patients required surgical revision.Conclusions: The vast majority of marginal ulcers had a favorable outcome after medical treatment. However, 9 % of patients eventually required surgical revision. Therefore, endoscopic follow-up is essential. Diabetes, smoking, and long gastric pouches were significant risk factors for marginal ulcer formation, suggesting increased acid exposure and mucosal ischemia are both involved in marginal ulcer pathogenesis. Management of these factors may prove effective in managing marginal ulcers, and tailoring postoperative proton pump inhibitor therapy to patients with multiple risk factors could be effective.